PENGARUH PROFITABILITAS, LIKUIDITAS DAN PELUANG PERTUMBUHAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Dwi Astarani Aslindar; Utami Puji Lestari (Faculty of Economic and Business Universitas STIKUBANK, 2020)
This study aims to examine the effect of profitability, liquidity and growth opportunities on firm value with capital structure as an intervening variable in the consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The sample was selected using purposive sampling technique. The number of samples is 13 companies or 65 data for 5 years. This study uses multiple linear regression analysis and path analysis. The results of hypothesis testing on capital structure show that profitability has no effect on capital structure, while liquidity and growth opportunities have an effect on capital structure. The results of hypothesis testing on firm value show that profitability and capital structure affect firm value, while liquidity and growth opportunities have no effect on firm value. The results of the analysis using path analysis show that profitability and growth opportunities affect firm value not through capital structure as an intervening variable, while liquidity affects firm value through capital structure as an intervening variable.